Dynamical Analysis of a Mathematical Model of COVID-19 Spreading on Networks - Li, Wang; Fu, Xinjie; Sun, Yongzheng; Liu, Maoxing (Frontiers in Physics, 2021)
In this paper an SEAIRS model to present the dynamics of COVID-19 epidemic on networks is established and analyzed. Following the method of the next generation matrix, we derive the basic reproduction number R_0, and it shows that the asymptomatic infector plays an important role in disease spreading. By theoretical analysis, we find that the disease-free equilibrium E_0 is asymptotically stable if R_0≤ 1; Moreover, the effects of various quarantine strategies are investigated and compared by numerical simulations. The results obtained are informative for us to further understand the asymptomatic infector in COVID-19 propagation and get some effective strategies to control the disease.